O właściwościach narracji filmowej - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
The aim of the article is to present a synthetic conception of film narrative both in the theoretical and practical context. The author considers the subject in terms of film theory and history. He also examines features of film narrative by using both the synchronous and diachronic method.